Resilience and Posttraumatic Growth of Patients With Breast Cancer During the COVID-19 Pandemic in China: The Mediating Effect of Recovery - Jing Shi; Kristin K. Sznajder; Shuo Liu; Xinyue Xie; Xiaoshi Yang; Zhen Zheng (Frontiers in Psychology, 2022)
PurposeThis study aims to examine the mediating role recovery plays in the relationship between resilience and posttraumatic growth (PTG) among breast cancer patients.MethodsA cross-sectional study design was implemented between January 02, 2021 and April 29, 2021. A total of 789 breast cancer patients from eight hospitals in Liaoning province were selected for participation in this study. These participants completed questionnaires, which included the Post-Traumatic Growth Inventory, EGO Resilience Scale and the Questionnaire about the Process of Recovery. The associated factors of PTG were analyzed using hierarchical multiple regression (HMR). The proposed relationships among resilience, recovery, and PTG were checked by structural equation modeling (SEM) analyses.ResultsThe average PTG score of breast cancer patients was 53.00 ± 28.30. PTG was positively correlated with both recovery and PTG (a*b = 0.1, BCa95% CI: 0.154 ∼ 0.054).ConclusionBreast cancer patients were found to exhibit a moderate degree of PTG. Resilience was positively associated with PTG and recovery mediated the positive effect of resilience on PTG. Resilience might serve as a crucial protective factor that could explain positive growth in life-threatening illnesses through the mediating path of recovery.